2019
DOI: 10.1186/s12885-019-6255-3
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for elderly patients with resectable pancreatic cancer, a comparison with non-surgical treatments: a retrospective study outcomes of resectable pancreatic cancer

Abstract: BackgroundWe designed a retrospective study to compare prognostic outcomes based on whether or not surgical resection was performed in elderly patients aged(≥75 years) with resectable pancreatic cancer.MethodsWe retrospectively analyzed 49 patients with resectable pancreatic cancer (surgery group, resection was performed for 38 cases; no surgery group, resection was not performed for 11 cases) diagnosed from January 2003 to December 2014 at the National Cancer Center, Korea.ResultsThere was no significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…The results proved that the overall survival of elderly patients was signi cantly shorter than the younger (14.68 months vs. 18.83 months, P < 0.001), while age is not the independent risk factor for elderly PDAC patients undergoing PD. This result was in agreement with some previous studies [16][17][18].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The results proved that the overall survival of elderly patients was signi cantly shorter than the younger (14.68 months vs. 18.83 months, P < 0.001), while age is not the independent risk factor for elderly PDAC patients undergoing PD. This result was in agreement with some previous studies [16][17][18].…”
Section: Discussionsupporting
confidence: 94%
“…For example, Park et al demonstrated that surgical resection signi cantly increased the survival of elderly patients when compared to non-surgical resection patients [18].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, aging itself was not an independent prognostic factor, and the non-frail elderly group showed comparable outcomes compared with the non-elderly group. Recently, the number of reports insisting that pancreatic resection of PDAC can be performed safely on older patients with acceptable risks is increasing [ 26 ]. However, frailty is a prognostic factor in several cancers [ 1 ], as shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As a highly malignant tumor, pancreatic cancer (PC) is the fourth leading cause of tumor-related death and is expected to become the second leading cause by 2030 in the US [ 3 , 4 ]. Due to the lack of clinical manifestations in the early stage, most PC patients are diagnosed at an advanced stage accompanied by metastasis [ 5 , 6 ]. Although the overall incidence of PC among all age groups is only 11.7 percent, the incidence of PC is 66.4 percent in patients over 65 years old and 91.1 percent in patients over 80 years old [ 7 ].…”
Section: Introductionmentioning
confidence: 99%